Neoadjuvant Treatment and Postoperative Complications After Surgery for Esophageal Cancer: A Population-Based, Nationwide Study in Finland - Sirviö, Ville E. J.; Räsänen, Jari V.; Helminen, Olli; Helmiö, Mika; Huhta, Heikki; Kallio, Raija; Koivukangas, Vesa; Kokkola, Arto; Lietzen, Elina; Meriläinen, Sanna; Pohjanen, Vesa-Matti; Rantanen, Tuomo; et al. (Springer Nature, 2026)
Background
The role of neoadjuvant treatment and its modalities in the risk of complications after esophagectomy in national practice is unclear. The aim of this study was to compare postoperative complications after neoadjuvant treatment (nT) and upfront surgery (US), neoadjuvant chemoradiotherapy (nCRT) and neoadjuvant chemotherapy (nCT), and to assess the effect of complications from neoadjuvant treatment in surgical risk.
Patients and Methods
All patients undergoing esophagectomy for esophageal cancer in Finland in 2005–2016 were included. Incidences of all postoperative complications defined by the Esophagectomy Complications Consensus Group as well as major complications, 90-day mortality, and hospital and ICU stay were reported stratified by treatment strategy (nT versus US, nCRT versus nCT, nT-complication versus no complication). Primary outcomes were compared using logistic regression in these patient groups.
Results
Out of 774 patients, 423 (55%) had nT and 351 (45%) had US. Of the 423 patients undergoing nT, 249 (59%) had nCT, 3 (1%) had radiotherapy only, and 171 (40%) had nCRT. After adjusting for relevant confounders, there were no increases in pneumonia, anastomotic leak, major complications, overall complications, or 90-day mortality with nT compared with US, nCRT compared with nCT, or in patients with nT complications compared with those without.
Conclusions
This nationwide, population-based study reports no difference in postoperative complications or mortality after nT compared with US or nCRT compared with nCT. Patients with neoadjuvant treatment complications were not at higher risk of postoperative complications.